Analisis Resepsi Foto Jurnalistik Konten Kericuhan di Stadion Kanjuruhan pada Instagram @TIRTOID - Fallah Akbar; Deviana Monica Jeane Destania (PT. Pustaka Cendekia Publisher, 2025)
This study examines the audience reception of photojournalism published by Tirto, focusing on journalistic photos that depict the chaos during the match between Arema Malang and Persebaya Surabaya at Kanjuruhan Stadium, Malang. Using a qualitative methodology with an analytical study approach, the research draws on Stuart Hall's reception theory. Six informants provided interpretations of the Kanjuruhan tragedy's content based on their social and cultural backgrounds. Findings reveal that audience understanding can be categorized into three positions: dominant hegemony, negotiation, and opposition. In the dominant position, the audience aligns completely with the media message. In the negotiation position, the audience accepts part of the message but also criticizes and rejects certain aspects. In the opposition position, the audience completely rejects the media message, replacing it with their understanding. This study offers valuable insights into media communication dynamics and the essential role of socio-cultural context in shaping audience reception of media content.